Tamil diaspora and the political spaces of second‐generation activism in Switzerland. (27th May 2014) - HESS, MONIKA; KORF, BENEDIKT
Abstract In this article, we study the emergence of the political spaces of activism of second‐generation Swiss Tamils resulting from a critical event – the suffering of Tamils during and after the final battle in early 2009 of a civil war in northern Sri Lanka that had lasted for decades. We contend that we can explain the geographies of newly emerging second‐generation activism committed to achieving Tamil Eelam through two factors. These are first, this generation's multiple senses of belonging both to Switzerland and to the Tamil 'nation' and, second, the way a specific politics of affect remoulded second‐generation identities because the pain of witnessing the brutality of war and suffering of Tamils occurred concurrently with a perceived lack of interest from their 'new home' (Switzerland). The combination of these factors made them want to acknowledge their Tamil 'roots' and encouraged them to become politically active. Consequently, these second‐generation activists primarily sought to engage with their host society – to awaken it from its indifference to the suffering of Tamils and from its passivity in taking action on an international level. We thereby witness the emerging of a new type of Tamil activism in Switzerland, which is firmly located in and bound to the host country.